Citra lelaki dulu dan kini dalam prosa Melayu: analisis teori relevans - Nor Hashimah Jalaluddin,; Norsimah Mat Awal, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
Much research has been done and written on women. However, the same cannot be said about men. Novels, as one of the sources of corpus, are able to portray the image of Malay men which to some extent mirrors reality. The Malay culture has always looked at a man as someone who is powerful, strong, a pillar of strength for women to depend on and is always “right” in his actions. All these perceptions give the impression that the world belongs to men, alone. These images are portrayed in such genres as television, classical novels, P. Ramlee films and even popular contemporary novels. It is obvious that there has been no paradigm shift in the portrayal of men in contemporary times. Relevance theory, a theory that focuses on information processing, is able to scientifically guide readers in understanding how these images of men are being portrayed. This article looks at images of men as depicted in films and novels through a relevance theory analysis to reaffirm the above mentioned perception. Explicatures and implicatures in the messages will be explicated to help understand Malay men, in particular.